Impact of total pancreatectomy: short‐ and long‐term assessment. Issue 11 (29th January 2013) - Barbier, Louise; Jamal, Wisam; Dokmak, Safi; Aussilhou, Béatrice; Corcos, Olivier; Ruszniewski, Philippe; Belghiti, Jacques; Sauvanet, Alain
Abstract Background The aim was to assess the outcome of a total pancreatectomy (TP). Methods From 1993 to 2010, 56 patients underwent an elective TP for intraductal papillary mucinous neoplasia (n = 42), endocrine tumours (n = 6), adenocarcinoma (n = 5), metastases (n = 2) and chronic pancreatitis (n = 1). Morbidity and survival were analysed. Long‐term survivors were assessed prospectively using quality‐of‐life (QoL) questionnaires. Results Five patients developed gastric venous congestion intra‐operatively. Post‐operative morbidity and mortality rates were 45% and 3.6%, respectively. An anastomotic ulcer occurred in seven patients, but none after proton pump inhibitor therapy. There were five inappropriate TPs according to definitive pathological examination. Overall 3‐ and 5‐year survival rates were 62% and 55% respectively; five deaths were related to TP (two postoperative deaths, one hypoglycaemia, one ketoacidosis and one anastomotic ulcer). Prospective evaluation of 25 patients found that 14 had been readmitted for diabetes and that all had hypoglycaemia within the past month. The glycated haemoglobin (HbA1c) was 7.8% (6.3–10.3). Fifteen patients experienced weight loss. The QLQ‐C30 questionnaire showed a decrease in QoL predominantly because of fatigue and diarrhoea, and the QLQ‐PAN26 showed an impact on bowel habit, flatulence and eating‐related items. Discussion Morbidity and mortality rates of TP are acceptable, although diabetes‐ and TP‐related mortality still occurs. Endocrine and exocrine insufficiency impacts on the long‐term quality of life.